Low dietary silicon supplementation may not affect bone and cartilage in mature, sedentary horses. (20th November 2020) - Pritchard, Abby; Nielsen, Brian D; Robison, Cara; Manfredi, Jane M
Abstract: As osteoarthritis is a major cause of lameness in horses in the United States, improving collagen health prior to onset and increasing collagen turnover within affected joints could improve health- and welfare-related outcomes. Through its positive effects on bone mineral content and density and its role in increasing collagen synthesis, silicon (Si ) may slow the development and progression of osteoarthritis, thereby reducing lameness. This study evaluated the hypothesis that Si supplementation would increase cartilage turnover through increased collagen degradation and formation markers, as well as bone formation markers, resulting in reduced lameness severity when compared with controls. Ten mature Standardbred geldings were assigned to either a Si-treated (SIL ) or control (CON ) group and group-housed on pasture for 84 d. Horses were individually fed to ensure no cross-contamination of Si other than what was present in the environment. For the duration of the study, SIL horses received a Si–collagen supplement at the rate of 0.3 g supplement/(100 kg body weight day). Serum samples were taken weekly for osteocalcin, and plasma samples were taken on days 0, 42, and 84 for plasma minerals. On days 0, 42, and 84, subjective and objective lameness exams were performed, and radiographs and synovial fluid samples were taken from reference and osteoarthritic joints. Plasma minerals were similar in both groups and were lower on day 84 than on day 0 ( P < 0.05). Si supplementation, fed at the manufacturer's recommended rate, did not improve lameness or radiographs when compared with controls, and supplemented horses did not show greater collagen degradation and/or synthesis markers in synovial fluid than controls, indicating that cartilage turnover remained unaffected. However, a minimum beneficial threshold and range for Si supplementation standardized to body weight need to be established.